The Role of Ethnopsychological Factors in the Formation of National Identity Among Adolescents - Qahramonova, Isomova Dilora (Indonesian Journal Publisher, 2025)
This article explores the role of ethnopsychological factors in the formation of national identity among adolescents. The study involved 9th-10th grade students from general education schools in the Samarkand region. The level of national identity and its influencing psychological factors – attitude toward the native language, historical memory, participation in cultural rituals, and the sense of belonging to an ethnic group – were assessed using diagnostic methods. Data analysis was carried out using SPSS software. Pearson correlation and factor analysis revealed that national identity is positively correlated with these factors. The results indicate that ethnopsychological approaches are essential for strengthening national self-awareness among youth.